The Analysis of the Transition from Field Rice Farming to Cassava Farming through a Land Optimization Development Program in Eelahaji Village Kulisusu District Buton Utara Regency - Fitriah; R. Marsuki Iswandi; Lukman Yunus (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2022)
This study aims to determine why farmers switch farming from field rice to cassava and determine the income difference between upland rice and cassava farming in Eelahaji Village, Kulisusu District, North Buton Regency. The study was conducted in Eelahaji Village, Kulisusu Subdistrict, North Buton Regency, in November 2021. The research population was all farmers receiving government assistance from the land optimization development program and 35 farmers who changed their farms. In contrast, the research sample was determined using the census method. The type and origin of the data used are primary and secondary data. Collecting data using the method of observation, interviews, and documentation. The research variables include income, cooperation of farmers in groups, farming habits, labor, production, costs, prices, and revenues. Analysis of the data used to answer the research objectives is descriptive analysis. The results of the study share that the reason for farmers to switch their farming is that the economic aspect uses a percentage (25%) in the form of 25% income and the social aspect with a percentage of 75% in the form of farmer cooperation in groups (25%), farming habits (25%) and labor ( 25%). The income of upland rice farming is on average IDR2,285,886/ha/year, while the income of cassava farming is on average IDR12,858,857/ha/year. Thus, it can be seen that there is a significant difference between the income of upland rice farming and cassava farming.